2006
DOI: 10.1536/ihj.47.363
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Amplitude of Intracardiac Ventricular Electrogram and Inappropriate Therapy in Patients With an Implantable Cardioverter Defibrillator

Abstract: SUMMARYIntracardiac electrograms are important for discrimination of tachyarrhythmia by implantable cardioverter defibrillators (ICD). A low R-wave can cause not only undersensing of ventricular tachyarrhythmia but also inappropriate discharges due to oversensing of unexpected signals because of its characteristic sensing algorithm. Therefore, this study aimed to investigate adverse events associated with R-wave amplitude. We included 115 consecutive patients followed-up over one year after implantation of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
(17 reference statements)
1
13
1
Order By: Relevance
“…From ICD interrogations, under-sensed low-amplitude VF seems to be the reason why long-term ARVC patients experience SCD without any ICD therapy 9, 10. This phenomenon may also play a role in our 3 index patients, although there was only 1 case in which we had available ICD recordings that documented intermittent under-sensed low-amplitude VF.…”
Section: Discussionmentioning
confidence: 90%
“…From ICD interrogations, under-sensed low-amplitude VF seems to be the reason why long-term ARVC patients experience SCD without any ICD therapy 9, 10. This phenomenon may also play a role in our 3 index patients, although there was only 1 case in which we had available ICD recordings that documented intermittent under-sensed low-amplitude VF.…”
Section: Discussionmentioning
confidence: 90%
“…90 In extensive RV disease, difficulty with lead placement or perforation may occur. A coronary sinus lead for pacing/sensing has been used in the event of low R waves.…”
Section: Icd Considerations Specific To Arvcmentioning
confidence: 99%
“…They demonstrated that the frequency of low R waves and also inappropriate therapy was high in arrhythmogenic right ventricular cardiomyopathy (ARVC) (38%), sarcoidosis (33%), and DCM (17%). 13 Wichter et al also suggested that particular attention should be paid to the progressive loss of the R wave amplitude during follow up in patients with ARVC. 14 Bramanti et al also reported that ARVC patients with pacemakers or ICDs should be closely followed in order to avoid any possible undersensing due to the extremely prolonged ventricular depolarization.…”
Section: Impact Of Pacing On the R And T Wave Amplitudes In Relation mentioning
confidence: 99%